Mariculture for bacterial and organic waste removal: a field study of sponge filtering activity in experimental farming. Issue 8 (4th December 2012) - Ledda, Fabio D; Pronzato, Roberto; Manconi, Renata
Abstract Culture experiments in the field were performed on western Mediterranean populations of Ircinia variabilis and Agelas oroides. To evaluate culture and filtering performances among polluted and unpolluted sites in shallow waters, farming experiments were carried out in a harbour, a small tourist nautical base and a pristine biotope. Sponge explants were cultured onto nylon ropes, and in situ clearance rate tests were performed on farmed sponges to assess filtering ability under diverse farming conditions. At the harbour site, sponge survival and growth were similar to that observed in the two unpolluted sites until early summer, when a rapid increase in explant mortality occurred in response to extreme variations in environmental conditions. Filtering experiments revealed high retention and clearance rates of I. variabilis and A. oroides at all sites. The highest rates were observed at the polluted site, reflecting the optimal metabolic performance of explants in the first phase of culture under stressful conditions. Our results highlight the feasibility of sponge microcosms and the ability of I. variabilis and A. oroides to clear large volumes of water of organic and bacterial loads in polluted sites.